Controversies in sonography diagnostic criteria in polyquistic ovary syndrome - Huerta-Sáenz, Igor Hermann (2022)
Polycystic ovary syndrome is a multifactorial disease. It is the most common endocrine disorder in women of childbearing age. This disease is mainly characterized by anovulation and hyperandrogenism, however several different clinical phenotypes can coexist and the intensity of the symptoms can vary. Currently, the finding of an ovary with polycystic morphology on ultrasound is one of the criteria for the diagnosis of PCOS according to the Rotterdam consensus (2003). This criterion is determined by the presence of ≥12 follicles within the ovary with a diameter of 2-9 mm and / or ovarian volume ≥ 10 cm3. Currently, with the development of new multifrequency transducers, it is possible to detect new and increasingly follicles in the ovary. Therefore, it is necessary to prepare new diagnostic guidelines specifically on the number of ovarian follicles needed to classify an ovary as a potential part of the syndrome. It is also necessary to rethink the definition of Ovaries with Polycystic Morphology by Polyfollicular since there is consensus that the cysts described in the ovarian morphology are not cysts but follicles.